1995
DOI: 10.3758/bf03214418
|View full text |Cite
|
Sign up to set email alerts
|

The advantage of first mention in Spanish

Abstract: An advantage of first mention-that is, faster access to participants mentioned first in a sentencehas previously been demonstrated only in English. Wereport three experiments demonstrating that the advantage of first mention occurs also in Spanish sentences, regardless of whether the firstmentioned participants are syntactic subjects, and regardless, too, of whether they are proper names or inanimate objects. Because greater word-order flexibility is allowed in Spanish than in English (e.g., nonpassive object-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
44
2
5

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 16 publications
6
44
2
5
Order By: Relevance
“…Although the NP1 probes and NP2 probes were in fact different names, the names were assigned to subject (NP1) and object (NP2) positions at random from pairs matched in length and perceived frequency (using norms collected by Gernsbacher). The effects in this study are similar in magnitude to those found in studies systematically investigating first mention effects (e.g., Gernsbacher & Hargreaves, 1988;Gernsbacher, Hargreaves, & Beeman, 1989;Carreiras, Gernsbacher, & Villa, 1995) in which the position of the names was systematically varied. There is no question of the first mention effect reported here being a materials effect.…”
Section: Discussionsupporting
confidence: 73%
“…Although the NP1 probes and NP2 probes were in fact different names, the names were assigned to subject (NP1) and object (NP2) positions at random from pairs matched in length and perceived frequency (using norms collected by Gernsbacher). The effects in this study are similar in magnitude to those found in studies systematically investigating first mention effects (e.g., Gernsbacher & Hargreaves, 1988;Gernsbacher, Hargreaves, & Beeman, 1989;Carreiras, Gernsbacher, & Villa, 1995) in which the position of the names was systematically varied. There is no question of the first mention effect reported here being a materials effect.…”
Section: Discussionsupporting
confidence: 73%
“…We have described those mental representations as structures, and we have proposed several general cognitive processes and mechanisms that enable comprehenders to build mental structures during comprehension (Gernsbacher, 1990;. According to the Structure Building Framework, comprehenders build coherent mental structures by first laying foundations (Carrieras, Gernsbacher, & Villa, 1995;Gernsbacher & Hargreaves, 1988;Gernsbacher, Hargreaves, & Beeman, 1989). Comprehenders then develop their mental structures by mapping incoming information onto their developing mental structures, when that incoming information coheres with or relates to the previous information (Deaton & Gernsbacher, in press;Foertsch & Gernsbacher, 1994;Gernsbacher, in press;Gernsbacher & Robertson, 1992).…”
Section: How Do Cataphoric Devices Improve Their Concepts' Representamentioning
confidence: 99%
“…For instance, main characters, usually introduced into the narrative by proper names, are more prominent and accessible than are secondary characters, introduced by role names (Anderson et al, 1983;Morrow, 1985b). Furthermore, first-mentioned characters are more accessible than are second-mentioned characters (Carreiras, Gernsbacher, & Villa, 1995;Gernsbacher & Hargreaves, 1988).…”
mentioning
confidence: 99%